Lahan Basah Buatan dengan Tanaman Paku Air (Azolla Microphylla) - Nadaa Puspitasari; Melati Ferianita Fachrul; Ratnaningsih Ratnaningsih (Jurnal Lingkungan dan Kota, 2021)
The aim of this research is to calculate density and growth rate, efficiency of COD, BOD, BOD5/COD ratio and values (r), (kA), and (kV). The research method used a horizontal flow type artificial wetland with Azolla microphylla plants and gravel and sand media. Wastewater comes from mixed wastewater from the inlet point. The reactor used consists of 3, namely, R0 (control), R1 (25% wastewater; 75% clean water), R2 (50% wastewater; 50% clean water). Acclimatization of plants with a load of 25% and 50% of the wastewater of each reactor with 40% initial cover area. The discharge of artificial wetlands is 51,84 m3/day. The results showed that the artificial wetland system with a load of 25% resulted in growth rates ranging from 0,1145 gr/day-0,1682 gr/day at a density of 37,04–118,52 ind/m2, the growth rate with a load of 50% between 0,1030 gr/day–0,2653 gr/day at a density of 37,04 ind/m2–103,70 ind/m2. COD efficiency at plant density with a load of 25% ranges from 15,89%-56,16%, BOD 14,26%-24,33% at a density of 37,04-118,52 ind/m2, COD efficiency with a load of 50% water waste 20,18%-29,55%, BOD 15,52%-22,65% at a density of 37,04-140,74 ind/m2. The removed organic load in COD parameters is 8294-20373 kgCOD/ha/day in reactor 1 and 15759-32348 kgCOD/ha/day in reactor 2, BOD is 7393-12612 kgBOD/ha/day in reactor 1 and 8046-18483 kgBOD/ha/day in reactor 2. Average COD in reactor 1 value (R) 6102 gr/m2/day, kA 38,58 m/day, kV 0,10/day. The average value of COD in the reactor 2 values (r) 8858 gr/m2/day, kA 53,41 m/day, kV 0,14/day. The value of BOD in the reactor 1 value (r) 3754 gr/m2/ day, kA 38,77 m/day, kV 0,10/day. In reactor 2 the average (r) was 4148 gr/m2/day, kA 44,09 m/day, and kV 0,11/day.